VALUL DE CĂLDURĂ DIN DECEMBRIE 1989 -STUDIU DE CAZ- (PANGEEA, 2025)
Heat waves are short episodes, but intense, of deviation by atmospheric air temperatures from the mean. Southern Romania is the geographic area most affected by this climatic phenomenon. The impact is particularly and has repercussions on the components of environment and on society.